Experimental and analytical studies on the response of freestanding laboratory equipment to earthquake shaking. - Konstantinidis, Dimitrios (Earthquake engineering & structural dynamics.)
This paper presents results of a comprehensive experimental program on the seismic response of full-scale freestanding laboratory equipment. First, quasi-static experiments are conducted to examine the mechanical behavior of the contact interface between the laboratory equipment and floors. Based on the experimental results, the response analysis that follows adopts two idealized contact friction models: the elastoplastic model and the classical Coulomb friction model. Subsequently, the paper presents shake table test results of full-scale freestanding equipment subjected to ground and floor motions of hazard levels with corresponding displacements that can be accommodated by the shake table at the UC Berkeley Earthquake Engineering Research Center. For the equipment tested, although some rocking is observed, sliding is the predominant mode of response, with sliding displacements reaching up to 60 cm. Numerical simulations with the proposed models are performed. Finally, the paper identifies a physically motivated intensity measure and the associated engineering demand parameter with the help of dimensional analysis and presents ready-to-use fragility curves.